AB0714 Validity of a simplified enthesitis ultrasound score in the diagnosis of spondyloarthritis. (23rd January 2014) - Haddouche, A.; Slimani, S.; Bendali, S.; Makhsoum, K.; Benmebarek, A.; Ladjouze-Rezig, A.
Abstract : Background: The Madrid sonography enthesitis index (MASEI) is a validated ultrasound score for the diagnosis of spondyloarthritis. It explores six entheses and thus requires about 20 minutes to be performed for each patient by a trained sonographist. Objectives: The aim of this study was to determine the validity of a simplified ultrasound score, limited to the exploration of two calcaneal sites (plantar aponeurosis and Achilles tendon), on Algerian spondyloarthritis (SpA), which is known to be more severe than European and north American one. Methods: A bi-center case-control study on SpA (Amor's criteria) patients was performed. Plantar aponeurosis and Achilles tendons were evaluated ultrasonographically (tendon thickness, structure, calcifications, erosions, Doppler Signal and bursitis) according to the description given for the MASEI score. Demographic and clinical parameters as well as pelvic X-rays were noted. A ROC curve was constructed in order to determine the cut-off value associated with the best sensitivity/specificity. Results: Twenty-one SpA patients (15 males) and 17 controls (12 men) were recruited. Mean BMI and age were similar in both groups. Mean disease duration was 8.7 ± 6.8 years. The mean simplified ultrasound score was 1.35 ± 1.46 in controls and 7.19 ± 3.44 in SpA patients ( p < 0.001). The area under the curve was highly significant (0.933; p < 0.001) and by choosing a cut-off value of ≥ 4 for positivity, we've obtained a sensitivity of 85.7% and a specificity of 94.2%. Radiographic sacro-iliitis had a sensitivity of 85%. among the 3 SpA patients without sacro-iliitis, 2 had a positive ultrasound score. Conclusions: This study shows that a simplified ultrasound score based only on the evaluation of calcaneal enthesitis is feasible for the diagnostis of SpA on Algerian patients, with a clear benefit on time gain (5 minutes vs 20 minutes for the MASEI). Disclosure of Interest: None Declared